A STUDY OF PARTICULARIZED CONVERSATIONAL IMPLICATURES IN POSTER - Tri Wijayanti; Hikmah Pravitasari (English Didactic, 2021)
The social circumstances of the conversations are significant. When chatting, the speakers must always make reference to those circumstances. Moreover, talks contain meanings that go beyond the utterances as well as literal meanings. This study explored the conversational implicatures in poster posted on the Facebook walls and websites. The data were analyzed using the social context and conversational implicature theories by Gricean typology of speaker meaning (Mey, 2009, p.365). In this investigation, various conversational implicatures were discovered. They include intentional disregard for the maxims, particularized conversational implicature, generalized conversational implicature, and standard implicature with the highest emergence. This study comes to the conclusion that the social circumstances of the participants, such as age, power or social standing, and social distance, have a significant impact on the usage of conversational implicature represented in the poster.